Melatonin Effects on Persistent Pulmonary Hypertension Induced Hypoxia - Mohamed Nofal , Sarah; Mohamed Abouelenain, Amany; Mohamed El-Mashad , Abdel-Rahman; Mohamed Awny , Mostafa; Mahmoud Elmesiry, Asmaa (Journal of Neonatal Surgery, 2026)
Background: Tissue hypoxia and insufficient perfusion can cause end organ damage in the systemic condition known as persistent pulmonary hypertension of neonates (PPHN), which has several causes. To diagnose hypoxia caused by PPHN and evaluate its improvement, changes in the high-mobility group box-1 (HMGB-1) protein can be used as a preliminary diagnostic marker. As a biomarker for disease severity and treatment response prediction, it may be pivotal in the hypoxia- and inflammatory-related pathophysiology of PPHN. The purpose of this study was to measure serum levels of high mobility group box-1 protein to determine the effects of melatonin in PPHN-induced hypoxia. Methods: This randomized-control study was conducted on 80 neonates ≥ 36 weeks of gestation, diagnosed with persistent pulmonary hypertension. The patients were split into two equal groups: Group I was given Melatonin, whereas group II got a placebo. Results: Melatonin significantly decreased serum HMGB levels compared to the control group. The melatonin group had a much shorter duration of mechanical breathing, oxygen support, and Neonatal Intensive Care Unit (NICU) stay compared to the control group. Also, Estimated Systolic Pulmonary Arterial Pressure (ESPAP) was significantly lower in the melatonin group than in control group. Conclusions: Melatonin can be used as an adjuvant therapy in PPHN and Hypoxic respiratory failure (HRF). Serum HMGB-1 levels can be used to prove melatonin’s positive effects in PPHN